The use of matic (automatic transmission of motorcycle) as catamaran boat engine to support economic activities in Ujung Pangkah, Gresik. (April 2018) - Sunardi,; Sukandar,; Setionohadi, B; Sulkhani, E; Sambah, A B; Pamungkas, S
Abstract: River is the only access to enter the pond area in Ujung Pangkah District, Gresik. The area is difficult to access due to the siltation of the river with only 50 cm depth. In addition, rent for traditional boat is expensive. This research developed a design of a small boat efficient enough to transport fish farmer from and to the pond area. Engine from motorcycle was used as it was easy to operate and economical use of fuel. The fundamental change for this design was a small double-hulled low-lane vessel. The motor matic engine was adjusted to a propeller to get maximum boost. The results showed that a ship with 3 meters length, 1.2 meters width and 1 m height, 2 persons in charge and speed of 7 knots, could use 150cc automatic motor engine by lowering engine rotation (RPM) from 7000 RPM to 4500 RPM using a Gear Box and 4-leaf B-Serries blades with a diameter of 14 cm.